The influence of money attitudes on young student consumers compulsive buying: Sabah perspective / Rusiyah Bandi - Bandi, Rusiyah (2012)
The discussion of the relationships between young student consumers' money attitudes and their compulsive buying will help marketers and policy makers to better understand these consumers' spending behavior. Thus, marketers can identify new market opportunities and form marketing strategies to target young student consumers'. On the other hand, to help young consumers to spend wisely the policy makers can also form more effective education strategies. Different from previous research in money attitudes and compulsive behavior, this research provides an overview of how male and female young student consumers perceive money and how their beliefs about money affect their spending on the 13-items Money Attitude Scales (MAS). Factor analysis yielded three factors: Power-Prestige, Retention-Time, and Quality were developed on the MAS. Reliability measures, multiple regression analysis, chi-square test, were determined and discussed. The analysis show that power-prestige, and quality dimension scale significantly affected on the young student consumers' money attitudes. The relationships on the influence between young student consumers' money attitudes (Power-prestige, Retention-time, and Quality) are salient predictor of compulsive buying behavior. Finally, young female students' consumers scored higher on compulsive buying behavior.